The Impact of Using Online Learning Software During the Covid-19 Pandemic in Higher Education - Natalie, Regina Yoantika; Mahendika, Devin; Salong, Amjad; Xu, Shanshan; Aji, Lexi Jalu (Journal International of Lingua and Technology, 2024)
The occurrence of covid-19 has a major effect on the smooth running of education, one of which is in higher education. So that lecturers and students need supporting media in the smooth learning process, such as the use of software. The use of software can make it easier for students to carry out the online learning process. This study aims to reveal the effect of using software on students in carrying out the distance learning process. In conducting this research, researchers used quantitative research methods with observations made in the form of distributing questionnaires to students to see the effect of software as a supporting medium in the learning process. The results of this study are that learning media using software is very helpful and has a good impact on students in the learning process during the covid-19 pandemic. The conclusion of this study is that fluency in the world of education during the co-19 pandemic is very limited, because students cannot integrate directly with lecturers in the learning process, therefore students and lecturers need media that can be used as supporting tools such as software for the smooth discussion and learning process, teaching in higher education. The limitation in this study is that researchers did not get accurate data in data collection. Therefore, it is hoped that future researchers will also conduct the same research in order to maintain relevant data results in analyzing the use of software in the learning process in higher education. This study also recommends that future researchers make this topic an ongoing discussion to obtain relevant and very effective research results so that this research can become a benchmark in the influence of using software as a learning medium during the covid-19 pandemic, so as to create a learning process based on supporting science and technology.